Ecological efficiency in glycerol combustion - Coronado, Christian R.; Carvalho, Joao A. [UNESP]; Quispe, Cesar A.; Sotomonte, Cesar R. (Elsevier B.V., 2014)
Growth in biodiesel production has led to a large surplus of glycerol. So the fundamental question arises: What can be done with glycerol? This is one of the main reasons current research is aimed at developing technologies for the conversion and/or use of glycerol in order to enhance the biodiesel industry and dramatically improve its profitability. This study evaluates and quantifies the environmental impact of glycerol combustion in biodiesel production plants that utilize boilers to produce thermal energy for the process. The concept of ecological efficiency mainly evaluates the environmental impact caused by CO2, SO2, NOx and particulate matter (PM) emissions. It is possible to calculate the quantitative environmental factor and the ecological effect of a biodiesel plant utilizing glycerol as boiler fuel. USP glycerin has the best ecological efficiency among the evaluated fuels while demethylated and methylated glycerols have the worst performance from the ecological point of view. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Glycerol; Combustion; CO2; Ecological efficiency; Pollutant